Blessings or curses? The contribution of the blesser phenomenon to gender-based violence and intimate partner violence - Frieslaar, Brent V. (HTS teologiese studies, 2021)
This article examines the blesser phenomenon in South Africa, which gained rapid popularity in 2016. A large body of research exists that reveals that transactional sex is a significant theme within the phenomenon of blesser and blessee relationships. Scholarship has demonstrated that transactional sex has contributed to an increase in human immunodeficiency virus infection rates, especially amongst women aged 15–24 years, as well as a concerning increase in teenage pregnancy. Whilst these are dire realities of blesser–blessee relationships, the one that is most concerning in the current climate in South Africa is the increase in gender-based violence (GBV), intimate partner violence (IPV) and femicide. Therefore, this article concerns itself primarily with this epidemic as it seeks to demonstrate how the blesser phenomenon contributes to GBV and IPV. Blessees are the young women in the blesser–blessee relationships who experience trauma and shame because of the violence and abuse inflicted on them by the older male blessers. The article argues that the church should be seen to be taking decisive action in addressing the scourge of GBV and IPV. The narrative approach is used to give the blessees the opportunity to share their stories. By applying the techniques of narrative therapy, positive deconstruction and the art of holy listening, the study reaches its key outcome: to offer to the church a framework for a pastoral care and healing methodology to help our sisters in Christ to experience healing and to move from shame to self-worth.Contribution: The Blesser phenomen has never been dealt with in theology, especially from the African perspective. Both sides of the problem need pastoral care. The major issue is where do we begin? I started, pastorally working with the blessee, who is in relationship with an older man. The main question that could be pastorally followed is, why pursue an older man for provision? This is a major pastoral issue, especially in poor communities. The younger women are in need of finance, in order to complete their studies and eke out a living. Beside the Covid 19 pandemic, this is the second major issue affecting black townships.